規訓權力的實踐─以教師專業發展評鑑為分析對象 The Power of Discipline: Some Thoughts on the Teacher Evaluation for Professional Development - 李孟倫 Lee, Meng-Lun (National Changhua University of Education, 2013)
教育改革的浪潮引發大眾對教師評鑑的關注，但教師評鑑雖以專業發展為號召卻隱含著權力宰制。這種權力並非刻板印象中透過強制或壓抑來施展，而是一種具有生產性，藉由一套看似無害之技術打造服從又有用的身體，即傅柯所主張的規訓權力。本研究擬由規訓權力的觀點來分析下列問題：一、教師評鑑中的規訓權力機制及其運作模式；二、教師評鑑所帶來的意識型態效果；三、接受評鑑的教師應對教師評鑑之方式。本研究發現：在教師評鑑過程中，規訓權力先將空間、人員切割、分類以便於監視，再依據規準進行裁決與改造以生產理想教師。對教師而言，評鑑如同一場競賽，因之產生競爭意識，有助於提升教師的表現更帶來自願順從的效果。 雖然表面上觀察不到反抗行動，但教師並非任憑擺佈，而是受制於現實因素無法進行全面性的公然反抗，故而改採非典型的反抗以回應教師評鑑。本研究之目的不在否定教師評鑑，而在提醒教師及關心此議題者隱藏於其中的權力運作，讓教師評鑑免於非教育因素的干擾，兼顧教師專業發展與自主以達成提升教學品質與學習成果 之功效。 Several waves of education reform in Taiwan lead us to care about the evaluation system that works on teachers. However, it is little known that the evaluation, as such, is a contested field, never taking consideration how a power structure works on a teacher in the name of enhancing his or her professional development. Most of all, the power structure thereof does not cause any noticeable oppression; it phases in subtle changes to remodel teachers. This paper attempts to raise following questions, basing on the theoretical framework of Foucaulian sense of power/discipline: 1. How does disciplinary power come about in the evaluation system? 2. What kind of ideology is there in the evaluation to make teachers compliant? 3. How could teachers who are under evaluation respond to the evaluation? This paper discovered that in the processes of evaluation, the disciplinary power came into effect to generate a set of ruling techniques and relevant criteria. For teachers, the evaluation was like a competition. It made them competitive, so as to enhance their performance spontaneously. Teachers reacted but, in reality, they had to adopt an atypical approach to resist. All in all, teachers' profession autonomy should be protected against the manipulation of power in the course of evaluation.